Development of professional language of students as means of forming of language personality of future teacher - Махінов, Віктор (Pedagogy of Higher and Secondary Education, 2015)
Makhinov V. N. Development of professional language of students as means of forming of language personality of future teacher. Research actuality is conditioned by meaningfulness of preparation of language personality of future teacher by the means of professional intercourse at the studies of foreign language as systems of knowledge, abilities and skills, that assist to development of sociocultural competence of students, forming of world view, moral and behavior, prepare to professional activity.